2021
DOI: 10.1002/cnr2.1533
|View full text |Cite
|
Sign up to set email alerts
|

L‐asparaginase doses number as a prognostic factor in childhood acute lymphoblastic leukemia: A survival analysis study

Abstract: Background The survival of children with acute lymphoblastic leukemia (ALL) has improved due to changes in the treatment and the disease diagnosis. A significant advance was the incorporation of asparaginase. However, hypersensitivity reactions are a common cause of early discontinuation of this drug. Aim The proposed study aims to evaluate early interruptions and the influence of the number of asparaginase doses effectively administered on the prognosis of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…It may be in line with data published by Dos Santos et al They found that children with ALL who received less than ten doses of ASP may be at an increased risk of treatment failure only if they were in a high-risk group. However, this study did not show statistical significance for the number of asparaginase doses in children with ALL who were at standard or medium risk [25]. These and our results may indicate that occurrence of acute pancreatitis in children with ALL is not a risk factor for leukemia relapse.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…It may be in line with data published by Dos Santos et al They found that children with ALL who received less than ten doses of ASP may be at an increased risk of treatment failure only if they were in a high-risk group. However, this study did not show statistical significance for the number of asparaginase doses in children with ALL who were at standard or medium risk [25]. These and our results may indicate that occurrence of acute pancreatitis in children with ALL is not a risk factor for leukemia relapse.…”
Section: Discussioncontrasting
confidence: 86%
“…Since using asparaginase in treating ALL improves event-free survival, its early discontinuation caused by AP or other toxicities may be associated with worse outcomes [23][24][25]. Although asparaginase was discontinued in 76.6% of patients with AP in our study, both disease-and eventfree survivals were comparable to patients who received remaining doses of ASP during subsequent therapy phases.…”
Section: Discussionmentioning
confidence: 70%